Awareness and Health Beliefs of Osteoporosis among Middle Aged Women in Selected Municipality of Kathmandu - Panta, Sarita; Adhikari, Sarita; Gurung, Anju; Pandey, Bimala; K.C., Amuba; Rai, Aruna (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Osteoporosis is a bone disorder characterized by a reduction in bone density accompanied by increasing porosity and brittleness. It is one of the major public health problem globally and its prevalence is rapidly increasing particularly in women. Osteoporosis causes more than 8.9 million fractures annually, resulting in an osteoporotic fracture every 3 seconds. Therefore the objectives of the study was to assess the existing awareness and health belief of osteoporosis among middle aged women. Methods: Descriptive cross-sectional research design was used on a sample of 328 middle aged women residing in Nagarjun Municipality, Kathmandu. Non probability purposive sampling technique was used to collect the data. Data was collected after informed consent through face to face interview schedule using Osteoporosis Knowledge Assessment Tool (OKAT) and Osteoporosis Health Beliefs Scale (OHBS). Descriptive statistics and inferential statistics (Chi-Square test) were used for data analysis at 5% level of significance. Results: The overall osteoporosis awareness and health beliefs mean scores were9.39 ± 2.93 and 146.18 ±11.58 respectively. Majority(60.0%) of the respondents were unaware of osteoporosis. Existing awareness of respondents was significantly associated with age (p<0.001and level of education (p<0.038). Based on the OHBS subscale score, the highest perception was on health motivation (22.73±2.81) and the lowest perception was on barriers to calcium intake (mean score 17.71±4.32). Conclusion: Based on the findings, it is concluded that the majority of middle aged women were unaware about osteoporosis. Education and age of women was significantly associated with level of awareness.